Edukasi Gizi Seimbang Dan Pemantauan Status Gizi Anak Usia 0-2 Tahun Pada Suku Anak Dalam (SAD) Desa Bukit Suban Kecamatan Air Hitam Kabupaten Sarolangun - Rumita Ena Sari; Fitria Eka Putri (Prodi Ilmu Kesehatan Masyarakat, FKIK Universitas Jambi, 2021)
Good nutritional status of toddlers plays an important role in growth and development, especially during the golden period in the first five years. Poor nutritional status of children under five can have a negative impact on physical and mental growth, decreased body resistance, and a more serious impact is the emergence of disability, high morbidity and accelerated mortality. Based on data from the Jambi Province Dinsosnakertrans (2010), one of the health problems that often occurs in the SAD community is the low nutritional status. Problems of poverty, low levels of education and lack of knowledge in the SAD community make them susceptible to diseases that also have an impact on their nutritional status. Efforts that can be made to improve nutrition improvement programs in remote indigenous communities are to provide education and information to all tribal communities in Bukit Suban Village about the importance of balanced nutrition by making food sources that exist in nature and easy for them to find as examples and then teach how to process them. food so that it can be consumed and still contains good nutritional value. Furthermore, monitoring the nutritional status of toddlers by measuring and weighing the toddler's weight. Based on interviews with people who initially did not know about good balanced nutrition for children, now they know a little and they also know how to use food ingredients that are in their environment and how to process food properly and hygienically. undernutrition by 31.25%